The Discipline of Tooth Brushing on Caries Prevalence in Children - Ferdinan Fankari; Emma Krisyudhanti (Dental Therapist Journal, 2024)
Indonesian people's brushing habits are still very concerning, as seen from the 2018 Basic Health Research data where only 2.3% of the population aged ≥ 10 years brushed their teeth after eating breakfast and before going to bed at night. This study aimed to determine the effect of tooth brushing discipline on the prevalence of caries in children of SD Negeri 2 Baumata Timur, Kupang Regency. This study is an experiment with a one-shot case study design, without a control group conducted on all 130 SDN 2 Baumata Timur students. All respondents were given an initial examination to determine dental caries (def-t/DMF-T) and were educated on brushing their teeth properly. Respondents were given control cards and stickers to be attached to the column after brushing their teeth in the morning after eating and the column brushing their teeth before going to bed at night for 120 effective days. Respondents will be evaluated for dental caries by re-examining dental caries (def-t/DMF-T) after brushing their teeth for 120 days, this aims to determine whether there are new caries after routine brushing activities carried out by the response. The results showed that the behavior of brushing teeth that was carried out consistently or the discipline of children brushing their teeth for 120 days by students at home was in the morning after eating and at night before going to bed. The results of the evaluation of dental caries after the intervention on regular brushing habits using oral health control cards showed that there was no risk of caries or new caries during 120 days of regular and consistent brushing.  The results of the Wilcoxon Signed Ranks Test statistical test showed a significant value of p 1.000> 0.05, so there was no difference before and after treatment using a dental health control card, but in substance there was an effect on caries prevention. The conclusion is that the discipline or consistency of children in brushing their teeth in the morning after eating and at night before bed can prevent dental caries in children.